The Effect of Dextrin Addition and Drying Temperature on the Processing of Cubed Palm Sugar) - Sardjono -; Joeswadi -; Elly Nurlaelyah (Balai Besar Industri Agro, 1988)
A study on the processing of cubed palm sugar had been carried out. The treatment done were dextrin addition (0.1% and 0.2%), drying temperature (60 degree and 80 degree celcius) and storage (0,2,4,6 and 8 weeks). The moisture content, reducing sugar and ash content were observed during 8 weeks storage. The best result was those with 0.1% dextrin addition and drying temperature 80 degree celcius for 45 minutes. After 8 weeks, the moisture content was 2.58-2.84%, reducing sugar 2.28-2.53% and ash content 0.58-1.02%.